1987
DOI: 10.1037/0021-9010.72.3.382
|View full text |Cite
|
Sign up to set email alerts
|

Examination of avoidable and unavoidable turnover.

Abstract: Dalton, Krackhardt, and Porter (1981) suggested that examining avoidable and unavoidable turnover could improve understanding and prediction of turnover. Unavoidable leavers and stayers in the current study were found to be no different from each other, whereas both groups were significantly different from avoidable leavers on levels of satisfaction, organizational commitment, job tension, and withdrawal cognitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
0
4

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(148 citation statements)
references
References 24 publications
5
139
0
4
Order By: Relevance
“…We include a number of person variables that are related to the development of links. For example, Abelson (1987) found that age, marital status, tenure, and having children were related to likelihood of staying. We also include a "links to community" construct that includes variables such as home ownership, community organization involvement, non-work friends in the community, and spouse's job.…”
Section: Need To Incorporate Job Embeddednessmentioning
confidence: 99%
“…We include a number of person variables that are related to the development of links. For example, Abelson (1987) found that age, marital status, tenure, and having children were related to likelihood of staying. We also include a "links to community" construct that includes variables such as home ownership, community organization involvement, non-work friends in the community, and spouse's job.…”
Section: Need To Incorporate Job Embeddednessmentioning
confidence: 99%
“…In the research of applied psychology, organization behavior and management treated turnover intention is rated as one of the most widely studied outcomes of job satisfaction and predictors of actual turnover behavior (Currivan, 1999). Compared to labor turnover that measures the rate of change in the workforce (Abelson, 1987), turnover intention focuses on workers' intention to withdraw from their job or organization, to look for other jobs or career alternatives. Turnover Employee Engagement intention can also be described as the probability of extending the individual's attachment to the occupation or organization.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…An employee's intention to leave an organization is related to his/her job satisfaction (Abelson, 1987;Arnold & Feldman, 1982;Baroudi, 1985;Sager & Johnston, 1989;Sager, Varadarajan, & Futrell, 1988). Further, employee evaluation criteria such as increased job performance, increased productivity, and decreased absenteeism are related to a higher level of an employee's job satisfaction (Brown & Peterson, 1994;Seashore & Taber, 1975;Singh, Verbeke, & Rhoads, 1996;Vroom, 1964).…”
Section: Job Satisfactionmentioning
confidence: 99%